2022
DOI: 10.3389/fnut.2022.812294
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Efficacy of the Capsaicin in Patients With Metabolic Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundPatients with metabolic syndrome (MetS) have increased cardiovascular risk. Capsaicin (CAP) has been shown to reduce lipids, but efficacy for patients with MetS is unknown.MethodsA systematic review was performed according to PRISMA guidelines, to compare the effects of CAP against a placebo. Differences in the weight mean difference (WMD) with 95% confidence intervals (95% CI) were then pooled using a random effects model.ResultsNine randomized controlled trials including 461 patients were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The increased serum levels of TG, TC, and LDL-c were risk factors for atherosclerosis, while HDL-c was considered as “good cholesterol” to exert an atheroprotective effect [ 22 ]. Our study showed that capsaicin significantly reduced the levels of TC and LDL-c, and increased the levels of HDL-c in serum, which was supported by previous studies [ 23 , 24 ]. Furthermore, proinflammatory cytokines participate in the early phase of atherogenesis [ 25 ], and macrophages intake of excessive ox-LDL will form foam cells, which stimulate the secretion of more proinflammatory cytokines [ 26 ]; this vicious cycle further aggravates the development of atherosclerosis.…”
Section: Discussionsupporting
confidence: 92%
“…The increased serum levels of TG, TC, and LDL-c were risk factors for atherosclerosis, while HDL-c was considered as “good cholesterol” to exert an atheroprotective effect [ 22 ]. Our study showed that capsaicin significantly reduced the levels of TC and LDL-c, and increased the levels of HDL-c in serum, which was supported by previous studies [ 23 , 24 ]. Furthermore, proinflammatory cytokines participate in the early phase of atherogenesis [ 25 ], and macrophages intake of excessive ox-LDL will form foam cells, which stimulate the secretion of more proinflammatory cytokines [ 26 ]; this vicious cycle further aggravates the development of atherosclerosis.…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of As is lower than the Chinese (<2.0 mg/kg), Brazilian (<0.6 mg/kg), WHO (<2.2 mg/kg), and American (<3.0 mg/kg) standards. To assess toxic metals in different types of tea, all types collected were analyzed, and the results revealed that the Cd in kuding tea, a traditional tea material widely used in China, had the highest concentration at 21.98 mg/kg, whereas As in jasmine tea had the highest As concentration at 0.76 mg/kg (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Capsaicin promoted vascular health by increasing nitric oxide (NO) production and reducing inflammatory responses. It also reduced low-density lipoprotein (LDL) levels, increased high-density lipoprotein (HDL) levels, and reduced oxidative stress levels in various tissues [126]. Capsaicin could lower low-density lipoprotein cholesterol (LDL-C), plasma cholesterol, and inhibits LPS-induced IL-1β, IL-6 and TNF-α production in a time-and dose-dependent [127][128][129].…”
Section: Cardiovascular Activitymentioning
confidence: 99%